THE SIGNIFICANCES OF ENGLISH STORTYTELLING IN PROMOTING THE YOUNG CHILDREN LITERACY - Aswadi Jaya (Jurnal Dosen Universitas PGRI Palembang)
AbstractBasically, children can learn language naturally even when theyhave not gone to the formal school yet. Parents and teachers shouldgive many different stimuli, such as telling them stories to promotetheir literacy. Every stimuli exposed to young learners will be such agood input toward their language development. As we know literacyis a foundation for lifelong learning. It is a tool of personalempowerment and a means for social and human development.However, several international literacy assessment institutionsfound that literacy rate in Indonesia was very low. Monotonous andboring classroom instructions seem to be among demotivatingfactors for young learners to learn. Children are naturally activelearners and thinkers. They learn best through interaction withpeers and learn effectively with adults. Storytelling may enable thiscondition since young learners love stories. This paper will discusscharacteristics of young learners and their learning experience aswell as the rationale for using storytelling to develop literacy inEnglish as a foreign language.Key words: Significance, promoting, literacy, young children, storytelling